MADDEN-JULIAN OSCILLATION (MJO) PROPAGATION IN MARITIME CONTINENT AND ITS RELATION TO COLD SURGE - Hairunnisa Norfahmi, Siti
This study examines the role of cold surge as one of the external forcings affects MJO propagation on the Maritime Continent. H?vmoller lag time analysis on MJO MC-crossing and non-MC-crossing events is performed using Interpolated OLR and horizontal wind data in ONDJFM 2000/01 - ONDJFM 2014/15 . The longer OLR value of -10 W/m2 shows deeper convection when MJOC compared to MJONC. Cold surge identification on MJO is defined used meridional data. The result shows that cold surge when MJO can lead the propagation to the East (MJOC). Statistical result shows 65% of all MJOC events are associated with cold surges. Based on Sea Level Pressure lag time on MJOC and cold surge (MJOC-CS), strongest northerly of cold surge is collided with eastward of MJO. Moisture transport lag time analysis on MJOC-CS shows that moisture convergence of cold surge and MJO is one of the reason the deeper convection of MJO to propagate across Maritime Continent (MJOC).